Changes in body composition with separate day combined strength and endurance training in men and women - Balandzic, Milica (2014)
The purpose of this thesis was to investigate changes in body composition during combined strength and endurance training performed on separate days. Forty previously untrained but physically active men and women took part in the study. The measurements were performed in the beginning of the training, after 12 weeks of training and after 24 weeks of training. The calculation of the body composition was done with using Dual X rays Absorimetry (DXA). The main findings in the study included the significant within group changes in lower body fat mass in both men (p<0.001) and women (p<0.01). Another finding included significant changes in trunk fat mass also in both men (p<0.01) and women (p<0.01). Along with that, trunk lean mass significantly increased in both men (p<0.001) and women (p<0.001). Maximal bilateral dynamic leg press significantly increased for both men (p<0.001) and women (p<0.001) as well as Vo2max for both groups (p<0.001). Women showed larger (p<0.05) gains than men. Between group increases occurred in maximal bilateral dynamic strength at mid and post periods. Similarly, women showed larger (p<0.05) increases in Vo2max than men at post period. In conclusion, 24 weeks of combined strength and endurance training on separate days resulted in improvements in body composition in both men and women. These changes also included contributions to increases in maximal strength and endurance performance. The present combined strength and endurance program can also have positive effects on overall health in previously untrained men and women.